Pengaruh Bimbingan Manasik Haji Terhadap Kemandirian Jemaah Haji di KBIHU Al-Magfiroh - Rahmayanti, Al Fini Aisyafar; Solahudin, Dindin; Aziz, Rohmanur (Mabrur: Academic Journal of Hajj and Umra, 2024)
The aim of this research is to determine the effect of ritual guidance provided by KBIHU Al-Magfiroh on the independence of the congregation at KBIHU Al-Magfiroh. The research method used in this research is a quantitative research method, with simple linear regression analysis. This research uses guidance theory according to Prayito and Erman Amti, that guidance is used as a process of assistance provided by a professional to individuals or groups. The results of this research show that the ritual guidance has effect on the congregation's independence by 72.4%. while remaining 27.6% is influenced by other variables outside this regression equation or variables that are not studied.